2021
DOI: 10.3390/v13030436
|View full text |Cite
|
Sign up to set email alerts
|

Early Administration of Convalescent Plasma Improves Survival in Patients with Hematological Malignancies and COVID-19

Abstract: The use of convalescent plasma in the treatment of COVID-19 may lead to a milder course of infection and has been associated with improved outcomes. Determining optimal treatments in high risk populations is crucial, as is the case in those with hematological malignancies. We analyzed a cohort of 23 patients with hematological malignancies and COVID-19 who had received plasma 48–72 h after the diagnosis of infection and compared it with a historical group of 22 patients who received other therapy. Overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 15 publications
0
42
0
Order By: Relevance
“…In contrast to RCTs, matched-control studies have generally observed a survival benefit associated with convalescent plasma therapy. Inspection of available Kaplan–Meier survival data from nine published matched-control studies showed a consistent pattern whereby convalescent plasma appeared to improve COVID-19 patient survival compared to non-transfused patients ( Figure 1 ) ( 50 , 52 , 59 62 , 64 , 69 , 70 ). Combining these available survival data demonstrated an 11% relative improvement in 28-day survival associated with convalescent plasma compared to control patients (82 vs. 74%) ( Figure 2C ).…”
Section: Convalescent Plasma Therapy For Covid-19: Mosaic Of Clinical Evidencementioning
confidence: 91%
See 3 more Smart Citations
“…In contrast to RCTs, matched-control studies have generally observed a survival benefit associated with convalescent plasma therapy. Inspection of available Kaplan–Meier survival data from nine published matched-control studies showed a consistent pattern whereby convalescent plasma appeared to improve COVID-19 patient survival compared to non-transfused patients ( Figure 1 ) ( 50 , 52 , 59 62 , 64 , 69 , 70 ). Combining these available survival data demonstrated an 11% relative improvement in 28-day survival associated with convalescent plasma compared to control patients (82 vs. 74%) ( Figure 2C ).…”
Section: Convalescent Plasma Therapy For Covid-19: Mosaic Of Clinical Evidencementioning
confidence: 91%
“…Qualitative inspection of the available Kaplan–Meier survival data from 16 controlled studies revealed a directionally consistent pattern whereby convalescent plasma transfusion was associated with greater patient survival compared to non-transfused patients ( Figure 1 ) ( 11 , 27 , 41 , 43 , 46 , 47 , 50 , 52 , 59 62 , 64 , 69 71 ). Pooling all available Kaplan–Meier survival data showed a 14% relative improvement in COVID-19 patient 28-day survival associated with convalescent plasma (84 vs. 74%) ( Figure 2A ).…”
Section: Convalescent Plasma Therapy For Covid-19: Mosaic Of Clinical Evidencementioning
confidence: 98%
See 2 more Smart Citations
“…For example, in a cohort study, an early administration of convalescent plasma improved survival in COVID-19 patients with hematological malignancies. 55 Additionally, in a nationwide observational multicenter study, the administration of convalescent plasma improved clinical outcomes in B-cell-depleted patients with protracted COVID-19. 56 Overall, these data suggested that application of convalescent plasma in COVID-19 might be limited.…”
Section: Immune System Modulation In Covid-19mentioning
confidence: 99%